SOSIALISASI PENINGKATAN HASIL USAHA MIKRO KECIL DAN MENENGAH (UMKM) MENGGUNAKAN MARKETPLACE DI PEKON SUKOHARJO 1 (LP3K Lampung, 2022)
Utilizing the marketplace for Micro, Small and Medium Enterprises (MSMEs) is very beneficial. With this marketplace, it can help business people to carry out promotions and marketing more broadly, not only in their area but nationally and internationally. Sukoharjo 1 is a village in Sukoharjo District, Pringsewu Regency, Lampung which has many MSMEs in it. Recognizing the lack of understanding and online marketing that causes the economy for them to be less stable, therefore the KKN team held Community Service (PKM) to introduce the benefits and uses of the marketplace or social media. This PKM was attended by 15 participants which was held at Balai Pekon Sukoharjo 1. With The existence of a marketplace can make it easier for sellers and buyers to transact quickly. There are 4 methods used in carrying out this service, namely: the lecture method, the tutorial method, the question and answer method and the literature study method. There were several things that were noticed in this activity, namely: the enthusiasm or good contribution of the participants, the attention and extraordinary responses from the participants both during the delivery of the material and the question and answer session or discussion and there was communication interaction from the presenters and participants who went well fluent. It is hoped that after holding this activity, the community, especially MSME actors, can take the knowledge that has been conveyed and take advantage of the use of the marketplace which can later increase sales through effective and efficient marketing.